Mold-making handbook - Mennig, Günter; Stoeckhert, Klaus, 1913- (Hanser Publications, 2013)
Specialist people from the industry have written this book. It will prove extremely useful for engineers, designers, processors, technical salesmen, and students interested in all aspects of mold construction.
Keywords: Plastics -- Molds.; elektronické knihy; electronic books